(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is relatively rare in children. Moreover, atypical presentation remains a diagnostic challenge for physician. Early recognition and proper immunomodulatory therapy is important for favorable outcomes with prevention of progressive course. We report a case with atypical CIDP. The aim was to focus on the diagnostic difficulties and the importance of recognizing this treatable condition. Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 64-66